ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PERSEPSI KUALITAS PRODUK DAN PERSEPSI HARGA MOBIL MITSUBISHI XPANDER DI KOTA PEKANBARU - Anthony Willy; Restuti Sri; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the level of customer satisfaction with perceived product quality and perceived price of Mitsubishi Xpander car in Pekanbaru City. The population in this study includes buyers and users of Mitsubishi Xpander car in Pekanbaru City. Primary data was collected by questionnaire as an instrument to prove the results of the research, to test the hypothesis in this study using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) with SPSS (Statistical Product and Service Solutions) software. The samples in this study amounted to 140 peoples. The sampling technique that has been selected is accidental sampling. The results showed that from the Importance Performance Analysis (IPA) method, it was known that in the Cartesian Diagram there were three attributes that require improvement and enhancement, the attributes were numbered 2, 3, and 8. There were six attributes that need to be maintained, the attributes were numbered 1, 4, 7, 10, 12, and 14. Based on the Customer Satisfaction Index (CSI) method, the overall level of customer satisfaction is 76.33% and that value is in the "Satisfied" category (60% - 80%), which means that the customer satisfaction level of the Mitsubishi Xpander car in Pekanbaru City is high.Keywords: Perceived Product Quality, Perceived Price, Customer Satisfaction, Importance Performance Analysis, Customer Satisfaction Index